Foreign language provision in English primary schools: making evidence-based pedagogical choices - Whiting, Sue B.; Marshall, Chloë Ruth (Frontiers in Education, 2023)
Fluency in more than one language is generally accepted as being advantageous in our modern global age. However, in addition to the obvious personal, social, cultural and economic benefits of being bilingual, it has been claimed that bilingualism enhances cognitive development in a range of areas relevant to educational outcomes. Given the poor track record of teaching children foreign languages in England, schools, that are not required to follow the National Curriculum, are understandably keen to investigate innovative methods for teaching languages, with the aim of not only enhancing language learning but also of stimulating heightened cognitive functioning. Our purpose in writing this paper is to arm education professionals with a critical awareness of the evidence supporting the bilingual advantage and innovative but unproven foreign language taster courses, in order to support them in making evidence-based pedagogical choices. We explain how young children effortlessly learn their first language(s) and argue that it is unrealistic to expect this process to be replicated in the foreign-language-learning classroom. We then review some of the evidence supporting the so-called ‘bilingual advantage’ and argue that the advantage is found in only specific, as yet undetermined, narrow circumstances and not in the bilingual population as a whole. We scrutinise the suitability of unproven foreign language taster courses for young children and argue that their claims are unlikely to be justified. Finally, we provide some objective criteria to help schools, from early years settings to the end of primary, to judge the efficacy of novel ways of teaching languages before adopting them.